TONAL LOGIC IN FRANZ SCHUBERT’S IMPROMPTUS (D 899) - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2017)
The present study approach the genre of Impromptu, making a brief introduction into the history of the genre. It describes the specific nature of this type of piano pieces, and made a tonal, analytical incursion in the Impromptus (D899) by Franz Schubert. By using some summary tables this study provides an overview of the pieces, regarding the tonal, tempo, metric, and extension. Separately, the table of the shapes provides a synthetic image of the architecture of the pieces. Then it follows a brief description of each piece.